Self-Esteem of Teens with Visual Impairments as a Predictor of Hardiness - Anastasia V. Miklyaeva; Irina A. Gorkovaya (Social Welfare: Interdisciplinary Approach, 2018)
The paper discusses the problem of visually impaired adolescents’ hardiness and its predictors. The results show that adolescents with visual impairments do not differ from “healthy” peers in terms of hardiness, however, their self-esteem is different from adolescents with normal vision. Predictors of hardiness are: idealized representations of one’s own health and well-being for blind adolescents; actual self-esteem of happiness and perspective self-esteem for adolescents with low vision; actual self-esteem of happiness and mirrored self-esteem for “healthy” adolescents.